Detection of chromosomal aberrations by fluorescence in situ hybridization in cervicovaginal biopsies from women exposed to diethylstilbestrol in utero. Issue 1 (1st January 2006) - Hajek, R. A.; King, D. W.; HernÁNdez-Valero, M. A.; Kaufman, R. H.; Liang, J. C.; Chilton, J. A.; Edwards, C. L.; Wharton, J. T.; Jones, L. A.
Abstract : Epidemiologic studies have associated estrogens with human neoplasms such as those in the endometrium, cervix, vagina, breast, and liver. Perinatal exposure to natural (17β-estradiol [17β-E2 ]) and synthetic (diethylstilbestrol [DES]) estrogens induces neoplastic changes in humans and rodents. Previous studies demonstrated that neonatal 17β-E2 treatment of mice results in increased nuclear DNA content of cervicovaginal epithelium that precedes histologically evident neoplasia. In order to determine whether this effect was associated with chromosomal changes in humans, the frequencies of trisomy of chromosomes 1, 7, 11, and 17 were evaluated by the fluorescence in situ hybridization (FISH) technique in cervicovaginal tissue from 19 DES-exposed and 19 control women. The trisomic frequencies were significantly elevated in 4 of the 19 (21%) DES-exposed patients. One patient presented with trisomy of chromosomes 1, 7, and 11, while trisomy of chromosome 7 was observed in one patient. There were two patients with trisomy of chromosome 1. Trisomy of chromosomes 1, 7, 11, and 17 was not observed in the cervicovaginal tissue taken from control patients. These data suggest that DES-induced chromosomal trisomy may be an early event in the development of cervicovaginal neoplasia in humans.